2021
DOI: 10.3389/fmicb.2021.708009
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptome Between Anti-drug Sensitive and Resistant Candida auris in China

Abstract: Candida auris emerged as a pathogenic species of fungus that causes severe and invasive outbreaks worldwide. The fungus exhibits high intrinsic resistance rates to various first-line antifungals, and the underlying molecular mechanism responsible for its multidrug resistance is still unclear. In this study, a transcriptomic analysis was performed between two C. auris isolates that exhibited different anti-drug patterns by RNA-sequencing, namely, CX1 (anti-drug sensitive) and CX2 (resistant). Transcriptomic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 62 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…We performed transcriptome analysis to explore the immunoprotective mechanism of ginsenoside Rg1 on the anti-cancer functions of granulocytes inhibited by NA ( 43 ). In this study, we performed a comparative RNA-seq analysis on four groups (NA group vs Control group, NA + Rg1 group vs NA group, and Rg1 group vs Control group) including 12 samples (Control 1, Control 2, Control 3, NA 1, NA 2, NA 3, Rg1 1, Rg1 2, Rg1 3, NA + Rg1 1, NA + Rg1 2, and NA + Rg1 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed transcriptome analysis to explore the immunoprotective mechanism of ginsenoside Rg1 on the anti-cancer functions of granulocytes inhibited by NA ( 43 ). In this study, we performed a comparative RNA-seq analysis on four groups (NA group vs Control group, NA + Rg1 group vs NA group, and Rg1 group vs Control group) including 12 samples (Control 1, Control 2, Control 3, NA 1, NA 2, NA 3, Rg1 1, Rg1 2, Rg1 3, NA + Rg1 1, NA + Rg1 2, and NA + Rg1 3).…”
Section: Resultsmentioning
confidence: 99%
“…We performed transcriptome analysis to explore the immunoprotective mechanism of ginsenoside Rg1 on the anti-cancer functions of granulocytes inhibited by NA (43). In this study, we performed a comparative RNA-seq analysis on four groups ( The screening conditions for differentially expressed genes are as follows: FC ≥ 2 and P < 0.05.…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…Of note, small transcriptomic alterations also occur among isolates with divergent antifungal susceptibility profiles ( 33 ). Also of note, a recent report detected almost 1,000 differentially expressed genes between azole-resistant and -susceptible C. auris isolates ( 65 ). This seems surprising as clade I as well as clade III isolates of C. auris display the lowest intraclade genetic diversities ( 13 ).…”
Section: Discussionmentioning
confidence: 98%
“…The complete genome of C. auris has been unveiled in recent years; therefore, research into the genes and gene products responsible for its virulence and pathogenicity remains limited. Studies indicate that numerous genes exhibit either upregulation or downregulation during the synthesis of lytic enzymes, such as phospholipase [34]. In a case report by Kumar et al (2015), proteinase, phospholipase, and hemolysin activity were determined in a C. auris strain isolated from vulvovaginal candidiasis [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that, as the biofilm matures, the genes encoding ABC transporter proteins like CDR1, SNQ2, and YHD3 become activated. Additionally, agglutinin-like sequence (ALS) proteins ALS1 and ALS5 may play a role in contributing to biofilm formation [34,45]. Biofilm studies with C. auris from different geographical clades confirmed that the biofilm-forming feature of C. auris is a critical virulence factor [38,46].…”
Section: Discussionmentioning
confidence: 99%